(untitled) (Scientific journal of the Fergana State University, 2023)
The article talks about the creation of archaeological parks as a form of museumization of archaeological objects, their features, principles and implementation, history. The experience of creating an archaeological park in some countries has also been studied. Museumification of archaeological heritage objects is considered on the basis of the experience of Belarus, Russia and Bulgaria. In particular, the creation of the Bereste Archaeological Museum dedicated to the culture of the medieval cities of Eastern Europe of the 13th century in Brest (modern Belarus), monuments in Bulgaria: the archaeological complex Nebet Tepe in Plovdiv, the architectural complex Old Nessebar - an archaeological reserve in Nessebar, the Abritus Archaeological Reserve in Varna and museum-reserve Tomskaya Pisanitsa in Russia, the archaeological park "Crossroads of the Worlds" in Altai. Archaeological parks are considered as a social phenomenon formed on the basis of foreign experience, and it takes a certain time to develop or study it. It will be appropriate if the upcoming works are planned before the creation of the park. Efficiency can be improved if activities such as research, project preparation, component identification, project implementation, funding, etc. are identified and then implemented. The creation of archaeological parks is a novelty for Uzbekistan. This can create its own difficulties.